Neurological Soft Signs in Type I Bipolar Disorder and Bipolar Spectrum Patients and Their Unaffected First‐Degree Relatives: A Cross‐Sectional Study - Seyed Saeed Sadr; Seyed Mehdi Samimi‐Ardestani; Yousef Semnani; Narges Adel; Faezeh Tajari; Nastaran Samani (Health Science Reports)
ABSTRACT Background and Aims This study aimed to compare neurological soft signs (NSSs) in type 1 bipolar disorder (BD), bipolar spectrum (BS) patients, and their unaffected first‐degree relatives. Methods This descriptive cross‐sectional study involved participants referred to the Psychiatric Department of Imam Hossein Hospital. Five groups (n = 25): patients with type 1 BD, patients with BS, unaffected first‐degree relatives of the two groups, and a control group were evaluated using the Neurological Evaluation Scale (NES). Results The analysis revealed that patients with bipolar I disorder had the highest NES scores, with significant group differences (F(4.120) = 10.36, p < 0.001). The Bonferroni correction identified bipolar I patients as the primary source of this difference, while other groups did not significantly differ. ANCOVA showed that age (F(1.123) = 3.92, p = 0.052) and gender (F(1.123) = 0.1, p = 0.75) had no significant influence on NES scores. However, all four NES subsets significantly contributed to the overall score, except for the sensory subset. Differences were significant between bipolar I patients and most other groups, except the BS group, which showed no significant differences from the rest. No correlation was found with age, gender, or age of disease onset. Conclusion The higher NSS severity in type I BD compared to BS and control groups highlights its potential link to the genetic and neurodevelopmental differences in BD type I. Further research is recommended.